An intravital microscopy model to study early pancreatic inflammation in type 1 diabetes in NOD mice. Issue 3 (1st September 2016) - Lehmann, Christian; Fisher, Nicholas B.; Tugwell, Barna; Zhou, Juan
ABSTRACT: Intravital microscopy (IVM) of the pancreas has been proven to be an invaluable tool in pancreatitis, transplantation and ischemia/reperfusion research. Also in type 1 diabetes (T1D) pancreatic IVM offers unique advantages for the elucidation of the disease process. Female non-obese diabetic (NOD) mice develop T1D spontaneously by 40 weeks of age. Our goal was to establish an IVM-based method to study early pancreatic inflammation in NOD mice, which can be used to screen novel medications to prevent or delay T1D in future studies. This included evaluation of leukocyte-endothelial interactions as well as disturbances of capillary perfusion in the pancreatic microcirculation.